Biomechanical analysis of walking gait when simulating the use of an Ilizarov external fixator. (June 2018) - Layton, Robin B; Stewart, Todd D; Harwood, Paul; Messenger, Neil
The Ilizarov frame is an external fixation device, primarily used for the treatment of complex fractures. The authors postulate that the size and weight of the frame may lead to biomechanical adaptations to gait, independent to any injury. Temporospatial characteristics, kinetics and kinematics were assessed when simulating the use of an Ilizarov frame. Fifteen healthy participants performed walking trials, with and without the simulated frame. Significant changes to temporospatial characteristics were identified, with a decreased mean walking speed (with: 1.24 m s –1 ; without: 1.29 m s –1 ) and increased mean step width (with: 0.14 m; without: 0.11 m). The push-off phase of gait differed significantly between test conditions with mean increases in ankle dorsiflexion angles (with: 90.4°; without: 89.0°) and extension moments (proportional to body weight or P BWT) at the knee and ankle (knee with: 0.8 P BWT·m; without: 0.7 P BWT·m; ankle with: 1.6 P BWT·m; without: 1.6 P BWT·m). Although changes were small and likely to be clinically insignificant, the size and weight of the frame led to adaptations which may be magnified for patient groups with associated injury and pain at the lower limb. Results provide an argument for the potential redesign of the frame.